STUDI PENDAHULUAN: PENGETAHUAN AWAL MAHASISWA PENDIDIKAN OTOMOTIF TENTANG TEKNOLOGI SEPEDA MOTOR LISTRIK: Indonesia, Inggris - Nabila Naila Fatin; Beni Setya Nugraha (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2024)
Abstract This study aims to identify the initial knowledge of students of the Department of Automotive Engineering Education FT UNY related to electric motorbikes. A quantitative survey method was used with a Likert scale questionnaire which included 10 statement items. The research respondents were students of the Department of Automotive Engineering Education FT UNY who were taking the Motorcycle Technology Course. The results showed that the level of initial knowledge was in the moderate category with an average score of 2.76. Some aspects such as hands-on experience and maintenance of electric motorcycles are low, while interest in learning more deeply is high. So, it is recommended to update the curriculum and study materials in the Semester Learning Plan (RPS) of the Motorcycle Technology Course, as well as the development of teaching tools to support students' understanding of electric motorcycle technology. Curriculum updates support SDGs 4, namely quality education by improving student competencies and aligning learning with industry needs. This research is also in line with SDGs 7, namely clean and affordable energy, through the introduction of environmentally friendly electric motorcycle technology to support clean energy. Keywords: initial knowledge, students, electric motorbikes Abstrak Penelitian ini bertujuan untuk mengidentifikasi pengetahuan awal mahasiswa Departemen Pendidikan Teknik Otomotif FT UNY terkait sepeda motor listrik. Metode survei kuantitatif digunakan dengan kuisioner skala Likert yang mencakup 10 item pernyataan. Responden penelitian merupakan mahasiswa Departemen Pendidikan Teknik Otomotif FT UNY yang sedang menempuh Mata Kuliah Teknologi Sepeda Motor. Hasil penelitian menunjukkan tingkat pengetahuan awal berada pada kategori sedang dengan rata-rata skor 2,76. Beberapa aspek seperti pengalaman langsung dan perawatan sepeda motor listrik rendah, sementara minat untuk belajar lebih mendalam tinggi. Sehingga direkomendasikan pembaruan kurikulum dan bahan kajian pada Rencana Pembelajaran Semester (RPS) Mata Kuliah Teknologi Sepeda Motor, serta pengembangan perangkat ajar untuk mendukung pemahaman mahasiswa terhadap teknologi sepeda motor listrik. Pembaruan kurikulum mendukung SDGs 4 yaitu pendidikan berkualitas dengan meningkatkan kompetensi mahasiswa dan menyelaraskan pembelajaran dengan kebutuhan industri. Penelitian ini juga sejalan dengan SDGs 7 yaitu energi bersih dan terjangkau, melalui pengenalan teknologi sepeda motor listrik yang ramah lingkungan untuk mendukung energi bersih. Kata kunci: pengetahuan awal, mahasiswa, sepeda motor listrik